2006
DOI: 10.1021/jp0643348
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering at the Silver Electrode/Ionic Liquid (BMIPF6) Interface

Abstract: This is the first report of in situ SER spectra of chemical species adsorbed on a Ag/room temperature ionic liquid (RTIL) interface. We have investigated the dependence of the SERS intensity of the RTIL derived from 1-n-butyl-3-methylimidazolium hexafluorophosfate (BMIPF6) adsorbed on a silver electrode. It has been shown that the BMI+ adsorbs on the silver electrode for potentials more negative than -0.4 V vs a Pt quasireference electrode (PQRE). In the -0.4 to -1.0 V potential range the SER spectra are simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 38 publications
8
106
1
5
Order By: Relevance
“…These techniques could be used to probe the EDL at the interface between an ionic liquid and single-layer or multilayer graphene with spatial resolutions down to 0.3 nm. Other types of experiments which could be used to shed light on the EDL interface include electron energy loss spectroscopy in a scanning transmission electron microscope 40 and surfaceenhanced Raman spectroscopy 41 . From the theoretical perspective, the substantial corrections to the capacitance values obtained from geometric considerations alone point to the importance of many-body effects influenced by electrode geometry and response properties for a complete understanding of energy storage at ionic liquid-electrode interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques could be used to probe the EDL at the interface between an ionic liquid and single-layer or multilayer graphene with spatial resolutions down to 0.3 nm. Other types of experiments which could be used to shed light on the EDL interface include electron energy loss spectroscopy in a scanning transmission electron microscope 40 and surfaceenhanced Raman spectroscopy 41 . From the theoretical perspective, the substantial corrections to the capacitance values obtained from geometric considerations alone point to the importance of many-body effects influenced by electrode geometry and response properties for a complete understanding of energy storage at ionic liquid-electrode interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with a huge enhancement factor (ca. 10 6 ) of surface signals from rough surfaces, SERS has also been applied to studies of ionic liquid systems [80][81][82] with sufficient detection sensitivity in the low-wavenumber region (down to ca. 100 cm À1 ), which is important to provide ion-surface bonding information at the electrode/ionic liquid interfaces.…”
Section: In Situ Characterizationmentioning
confidence: 99%
“…[86] Despite the necessity of using rough surfaces for enhancement, SERS has also been used to study the adsorption behavior of solvent ions on rough Ag in [BMI] [PF 6 ] by Rubim and coworkers. [80] It is shown that the BMI + cation adsorbs on the Ag surface with the imidazolium ring moving from nearly perpendicular to almost parallel to the surface as the electrode potential is made more negative.…”
Section: Spectroscopic Investigation Of Adsorption Orientationmentioning
confidence: 99%
“…[49 -54] Therefore, it provides a powerful technique for studying the interfacial structure on different surfaces at the monolayer or submonolayer level. To the best of our knowledge, there was only one report which was concerned with the RTIL system directly, by Santos et al [24] They presented the first report of in situ SERS studies on the chemical species adsorbed on the Ag/RTIL interface. They investigated the dependence of the SERS intensity of the RTIL derived from 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF 6 ) adsorbed on an Ag electrode roughened in the presence of [BMIM]PF 6 as well as the potential dependence of pyridine adsorbed on Ag electrode in [BMIM]PF 6 at relatively negative potential region.…”
Section: Introductionmentioning
confidence: 99%